Sci-Tech Communication: Is There a Process of Internationalization in English and Spanish? - Mendiluce-Cabrera, Gustavo; Bermúdez-Bausela, Montserrat (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractClearly, English is the lingua franca adopted by the scientific community. More specifically, it is International English (IE), the specialized language that non-native users of English need to acquire in order to be accepted by this community. From this starting point, we will discuss the presence or absence of diatopic variants in sci-tech written language as illustrated in the field of Medicine. Despite this linguistic uniformization, translation is still extremely important in LSP, as software localization shows. Yet, companies that localize from English into Spanish agree on the importance of finding a universal variety of Spanish to reduce costs. Thus, Medicine and software localization show how this complex process of internationalization works in two different specialized languages.